23 PENGGUNAAN MODEL LISTENING TEAM SEBAGAI SARANA MENINGKATKAN KEMAMPUAN BERTANYA PADA PEMBELAJARAN IPA SISWA KELAS X SMK YP 17-2 MADIUN - Ida Mafikha Sari (UNIVERSITAS PGRI MADIUN, 2015)
Implementation of Vocational Education in Madiun 17-2 YP use the lecture method, so that the activity asks students less. The aim of research to improve the ability to ask students in learning science. Qualitative research approach used classroom action research (PTK), which consists of two cycles. The subjects included 23 students, collecting data using observation sheets to determine the ability to ask, student activities, and the quality of learning. The research result an increase in the ability to ask the first cycle of 50%, 69.56% second cycle. Student activity 62% cycle I Cycle II 73.91%, active criteria. The quality of learning cycle I cycle 71% II 80%. Conclusion The results of the research team use listening learning model can improve the ability to ask.